2020
DOI: 10.1001/jamaoto.2020.0047
|View full text |Cite
|
Sign up to set email alerts
|

Intratympanic vs Systemic Corticosteroids in First-line Treatment of Idiopathic Sudden Sensorineural Hearing Loss

Abstract: IMPORTANCETo our knowledge, evidence-based recommendations on the intratympanic vs systemic administration of corticosteroids for the treatment of idiopathic sudden sensorineural hearing loss remain unestablished, and contradictory conclusions have been reported in previous meta-analyses.OBJECTIVE To compare recovery from idiopathic sudden sensorineural hearing loss based on systemic, intratympanic, or a combined treatment with corticosteroids as first-line treatment.DATA SOURCES We adhered to the Preferred Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(42 citation statements)
references
References 37 publications
(141 reference statements)
0
42
0
Order By: Relevance
“…Once they had been referred to our ENT Department for the sudden onset of SSNHL, all patients received oral high dose prednisone therapy (60 mg/day) [ 31 , 32 , 33 ], oral mesoglycan (50 mg, twice a day) [ 34 , 35 ] and Hyperbaric Oxygen Therapy (HBOT) [ 36 , 37 , 38 , 39 ]. During HBOT, 100% oxygen was provided at a pressure of 2.5 ATA, in sessions of 1 h per day.…”
Section: Methodsmentioning
confidence: 99%
“…Once they had been referred to our ENT Department for the sudden onset of SSNHL, all patients received oral high dose prednisone therapy (60 mg/day) [ 31 , 32 , 33 ], oral mesoglycan (50 mg, twice a day) [ 34 , 35 ] and Hyperbaric Oxygen Therapy (HBOT) [ 36 , 37 , 38 , 39 ]. During HBOT, 100% oxygen was provided at a pressure of 2.5 ATA, in sessions of 1 h per day.…”
Section: Methodsmentioning
confidence: 99%
“…However, recent meta-analysis showed negative results regarding the effect of steroids. 13,14) Althouth the risk-to-benefit ratio and the efficacy of steroids remain obscure, some large observational studies showed beneficial effects of its use in ISSNHL. Therefore, recent clinical guidelines suggest that steroid therapy within two weeks of symptom onset could be an option for the treatment of ISSNHL.…”
Section: Discussionmentioning
confidence: 99%
“…Corticosteroids work by reducing inflammation, edema, modulating the immune system in the inner ear, increasing the microcirculation of the inner ear, having an antioxidant effect, and playing a role in ion and water homeostasis. 2,22,24 Corticosteroids also aim to improve nerve function. Corticosteroids reach the inner ear via a systemic route via intratympanic steroid injection and increase blood flow to the inner ear.…”
Section: Methodsmentioning
confidence: 99%